Monitoring in coastal environments using Foraminifera and Thecamoebian indicators - Scott, D. B. (Cambridge University Press, 2001)
The first book in this field to emphasize the methodological approaches being used for environmental applications of foraminifera and thecamoebians. Its main audience will include researchers and consultants, but it will also serve as a supplementary text for graduate students in courses that deal with environmental monitoring and assessment.